Joint and several liability for labour obligations in employer groups, doctrine and jurisprudence; the peruvian case - Valdivia Corzo, María Gracia (2022)
Technological changes, scale production and productive decentralization entail new forms of cooperation and coordination between capital and labor, but at the same time imply new social realities on which the law must operate, in this case the transformation of the figure of the employer is affected and therefore the way in which labor obligations are configured, the present work aims to analyze the national form in which this phenomenon is presented through the joint and several liability of the economic groups, the present research is of a correlational-explanatory type and scope, the bases of the analysis are normative, doctrinal, jurisprudential and documentary, likewise the instrument used consisted of a questionnaire with structured questions addressed to 52 lawyers specialized in labor law.